Pengaruh Profitabilitas, Ukuran Perusahaan, Dan Pertumbuhan Perusahaan Terhadap Corporate Social Responsibility (CSR) - Kormen, Adzima Salsa Haliza; Anik, Sri (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
Corporate Social Responsibility (CSR) has rapidly emerged as a significant priority in the corporate realm, particularly for corporations in the mining industry that directly affect the environment. This research seeks to analyze the impact of profitability, business size, and growth on CSR disclosure among mining firms listed on the Indonesia Stock Exchange (IDX) for the period of 2022-2023. A quantitative methodology using an explanatory study design and multiple linear regression analysis was used to evaluate the hypotheses. The findings indicate that profitability, as assessed by Return on Assets (ROA), substantially affects CSR disclosure, although firm size and expansion have no significant impact. The data indicate that, despite the expectation for big or high-growth businesses to engage more in CSR, severe rules in the mining industry have a more significant impact on CSR disclosure. This research offers significant insights into the determinants of CSR disclosure within a heavily regulated industry.